Faecal miRNA profiles associated with age, sex, BMI, and lifestyle habits in healthy individuals - Francavilla, Antonio; Gagliardi, Amedeo; Piaggeschi, Giulia; Tarallo, Sonia; Cordero, Francesca; Pensa, Ruggero G.; Impeduglia, Alessia; Caviglia, Gian Paolo; Ribaldone, Davide Giuseppe; Gallo, Gaetano; Grioni, Sara; Ferrero, Giulio; et al. (Scientific reports, 2021)
For their stability and detectability faecal microRNAs represent promising molecules with potential clinical interest as non-invasive diagnostic and prognostic biomarkers. However, there is no evidence on how stool miRNA profiles change according to an individual’s age, sex, and body mass index (BMI) or how lifestyle habits influence the expression levels of these molecules. We explored the relationship between the stool miRNA levels and common traits (sex, age, BMI, and menopausal status) or lifestyle habits (physical activity, smoking status, coffee, and alcohol consumption) as derived by a self-reported questionnaire, using small RNA-sequencing data of samples from 335 healthy subjects. We detected 151 differentially expressed miRNAs associated with one variable and 52 associated with at least two. Differences in miR-638 levels were associated with age, sex, BMI, and smoking status. The highest number of differentially expressed miRNAs was associated with BMI (n = 92) and smoking status (n = 84), with several miRNAs shared between them. Functional enrichment analyses revealed the involvement of the miRNA target genes in pathways coherent with the analysed variables. Our findings suggest that miRNA profiles in stool may reflect common traits and lifestyle habits and should be considered in relation to disease and association studies based on faecal miRNA expression.